Efektivitas Metode Inkuiri dengan Bantuan ChatGPT dalam Meningkatkan Keterampilan Menulis Teks Deskripsi Siswa - Anggle Anggllina Putri; Ida Ayu Made Wedasuwari; Ni Wayan Eminda Sari (Universitas Nahdlatul Wathan Mataram, 2026)
This study aims to determine the effectiveness of the ChatGPT-assisted inquiry method in improving the descriptive writing skills of seventh-grade students in Class VII B at SMP PGRI 2 Denpasar. This study is a classroom action research project consisting of the planning, action, observation, and reflection phases. Data were collected through tests, observations, questionnaires, and documentation, then analyzed using descriptive quantitative and qualitative methods. The results indicate an improvement in students’ writing skills, with an average pre-test score of 53.4, increasing to 81.94 in Cycle I, and 90.19 in Cycle II. Student engagement also increased from 58.78% (sufficient category) in Cycle I to 83.78% (very good category) in Cycle II. Student responses to the implementation of this method were very positive, with a percentage of 85.80%. This study contributes an alternative technology-based learning innovation that teachers can utilize to improve students’ writing skills more effectively and interactively.